Shaping the Workforce of Tomorrow : A Comprehensive Review of Competence-Based Learning for Employability Enhancement - Wisudani Rahmaningtyas; Soetarno Joyoatmojo; Kristiani Kristiani; Tri Murwaningsih; Leni Noviani (Universitas Pendidikan Mandalika (UNDIKMA), 2023)
This research aims to provide a comprehensive overview of competence-based learning in improving future employability skills and explain the basic concepts, principles, and the relevance of this approach in addressing rapid changes in the workplace. The research method used is a literature review with qualitative based on searching and analyzing relevant scientific articles, books, and publications related to competence-based learning and employability skills. The search was conducted through electronic academic databases such as Emerald, Scopus, Elsevier, Web of Science, ScienceDirect, Sinta, and ResearchGate using keywords